2020
DOI: 10.1177/0275074020919908
|View full text |Cite
|
Sign up to set email alerts
|

Police Use of Force Interactions: Is Race Relevant or Gender Germane?

Abstract: Representative bureaucracy research has examined the influence of race and ethnicity on policing outcomes, yet little is known about police use of force specifically at the individual-level. To address this topic more meticulously, we utilize individual-level data (from Indianapolis and Dallas police departments) to explore differences in the amount of force used by officers in ethnic, racial, and gender matches in police–civilian dyads. Findings suggest that there are heightened levels of force used when ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 73 publications
0
41
0
Order By: Relevance
“…At the organizational level, we contend that professions that only commit to symbolic representation will not automatically gain any positive responses from clientele. Recent scholarship on policing and race has found that even some of the most diverse police departments do not produce all of the intended benefits for people of color related to use of force, civilian complaints, or trust (Sharp and Johnson 2009;Wright 2020;Wright and Headley 2020). Further, it may be possible that symbolic representation without an active commitment to organizational change may result in worse outcomes for marginalized communities.…”
Section: The Micro-theory Of Symbolic Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…At the organizational level, we contend that professions that only commit to symbolic representation will not automatically gain any positive responses from clientele. Recent scholarship on policing and race has found that even some of the most diverse police departments do not produce all of the intended benefits for people of color related to use of force, civilian complaints, or trust (Sharp and Johnson 2009;Wright 2020;Wright and Headley 2020). Further, it may be possible that symbolic representation without an active commitment to organizational change may result in worse outcomes for marginalized communities.…”
Section: The Micro-theory Of Symbolic Representationmentioning
confidence: 99%
“…In the United States, modern policing is rooted in slave patrols and night watches that kept people of color under control, particularly in Southern states (Headley 2020). Even after the first formal organized police forces were started in the mid-1800s in places such as New York City, New Orleans, Cincinnati, Boston, Philadelphia, Chicago, Milwaukee, and Baltimore, they were monolithic, comprised of all-White and all-male officers.…”
Section: The Case For Race and Policementioning
confidence: 99%
“…The representative bureaucracy literature focused on the organizational or aggregate level has generally been associated with improved performance and outcomes (Hong 2016; Keiser et al 2002). Comparatively fewer studies have examined the effects of individual‐level demographic or identity matching between bureaucrats and civilians and these studies provide mixed support (Guul 2018; Wright 2019; Wright & Headley, 2020).…”
mentioning
confidence: 99%
“…Yet, personal level factors do not entirely explain disparities -organizational dynamics and culture, unchecked discretion and limited oversight on administrative practices (e.g., kneeling on someone's neck to subdue them), policies, chains of command, levels of scrutiny, formal and informal messaging, as well as elected leader and community messaging all combine to produce multiple points of disadvantage in which Black people -whether encountered on the street or even serving within departments -are less likely to receive the equal protection of the law (Glaser, 2014;Headley, 2020). As encapsulated by Wright and Headley (2020), race is relevant when considering police-community relations. Recent police killings are the unjust outputs of systems that have been hallmarked from the beginning by racism and white supremacy; and the aloofness as well as dirty hands of public administrators must be met with an ethic of care, respect, and a rewriting of the social contract to ensure that everyone, not just the privileged, benefit from public policies (Alkadry & Blessett, 2014;Blessett et al, 2016;McCandless & Ronquillo, 2019).…”
Section: Institutional Racism At a Glance: Policingmentioning
confidence: 99%